Efficacy of discontinuing the use of low‐dose aspirin at 28 weeks of gestation for preventing preeclampsia. Issue 11 (10th August 2022) - Kawaguchi, Haruna; Kanagawa, Takeshi; Yamamoto, Ryo; Sasahara, Jun; Okamoto, Yoko; Mitsuda, Nobuaki; Ishii, Keisuke
Abstract: Aim: Low‐dose aspirin (LDA) has been shown to reduce the incidence of preeclampsia (PE). Previous studies have focused on the timing of LDA initiation, but no study to date has assessed the timing of LDA discontinuation. This study aimed to evaluate the effect of LDA when LDA is initiated between 12 and 16 weeks of gestation and continued until 28 weeks of gestation. Methods: This prospective cohort study with historical controls investigated singleton pregnancies that were at a high risk for PE. High‐risk factors were defined as a history of hypertensive disorders of pregnancy, chronic hypertension, diabetes mellitus, autoimmune disease, obesity, and high normal blood pressure in the first trimester. We performed adjustments using propensity score matching (PSM) for each indication of LDA, maternal age, primiparity, and assisted reproductive technology. The primary outcome was the incidence of PE. Secondary outcomes were the incidence of preterm PE, fetal growth restriction (FGR), preterm birth, fetal malformation, and maternal postpartum hemorrhage (PPH). Results: A total of 203 and 543 participants were assigned to the LDA and control group, respectively. After PSM, there was no significant difference in the incidence of PE (22.0% vs. 16.8%; p  = 0.20), preterm PE (12.0% vs. 13.1%; p  = 0.76), FGR (7.9% vs. 12.0%; p  = 0.17), or preterm birth (17.3% vs. 15.7%; p  = 0.68). There was also no significant increase in maternal PPH or in the incidence of fetal malformations. Conclusion: Discontinuing the use of LDA at 28 weeks of gestation did not result in a lower incidence of PE and FGR.